Room‐Temperature Linear Light Upconversion in a Mononuclear Erbium Molecular Complex. (18th October 2018) - Golesorkhi, Bahman; Nozary, Homayoun; Guénée, Laure; Fürstenberg, Alexandre; Piguet, Claude
Abstract: To date, the piling up of successive photons of low energies (near infrared; NIR) using a single lanthanide center and linear optics to ultimately produce upconverted visible emission was restricted to low‐phonon solid materials and nanoparticles. Now we show that the tight helical wrapping of three terdentate N‐donor ligands around a single nine‐coordinate trivalent erbium cation provides favorable conditions for a mononuclear molecular complex to exhibit unprecedented related upconverted emission. Low power NIR laser excitations into the metal‐centered transitions Er( 4 I11/2 ← 4 I15/2 ) at 801 nm or Er( 4 I13/2 ← 4 I15/2 ) at 966 nm result in upconverted blue–green emissions, where two or three photons respectively are successively absorbed by a molecular lanthanide complex possessing high‐energy vibrations.